Sex differences in alcohol use and perceptions of cognitive health in rural Uganda - Emmanuel Maleka; Julius Kyomya; Joyce Namwase; Humphrey Beja; Samantha Mary; Godfrey Zari Rukundo; Edith K. Wakida; Celestino Obua (BMC geriatrics, 2026)
Background Dementia is a significant public health issue affecting over 50 million people worldwide. Alcohol consumption has been identified as a modifiable risk factor for dementia and its progression. This study aimed to explore the sociocultural factors influencing sex differences in alcohol consumption and community perceptions of its potential cognitive effects, including dementia risk in rural Uganda, where alcohol use is prevalent. Methods We employed a qualitative study design in the Ibanda and Lira districts, guided by the Gender Analysis Framework (GAF). We conducted in-depth interviews with 20 older adults (aged 60 years or older) who consume alcohol and 10 key informant interviews with community leaders. We used a deductive thematic analysis approach to generate themes and sub-themes using GAF. Results Four main themes are presented in this study: Access to resources, Practices and participation, Beliefs and perceptions, and Institutions, Laws and Policies. We found that men had greater access to alcohol due to their economic independence and social norms, often drinking in social settings. This was facilitated by peer relationships and the acceptance of drinking as a social norm for men. Women’s access to alcohol is limited by household responsibilities and cultural expectations, with consumption mainly at home and in smaller quantities. Community norms discourage alcohol consumption by women and are associated with shame and family disruption. Most participants believed that alcohol could cause memory problems, although some felt that other factors, such as age, could contribute to cognitive decline. Weak enforcement of alcohol regulations and religious influences were noted, with women reported to be more receptive to religious guidance on quitting alcohol consumption. Conclusions Gender disparities exist in alcohol access, consumption patterns, and social norms in rural Uganda. Participants commonly associated alcohol use with forgetfulness and short-term memory problems, perceptions that are consistent with early cognitive effects of alcohol but not with later stages of dementia. There is a need for gender-specific interventions to address alcohol consumption and to raise awareness about its potential impact on cognitive health in this population.
Keywords: Alcohol use; Alcohol use disorder; Dementia; Gender; Sex; Older adults; Rural Uganda